Mathematical Rigor at Primary Level in Pakistan: Teachers Problems and Prospects - Dildar Hussnain; Dr. Uzma Shahzadi; Dr. Bashir Hussain (`, 2025)
The importance of teachers in the contemporary world has assumed novel manifestations due to the advent of the modern period. The main purpose of this research study was to investigate the mathematical rigor at primary level in the district Khushab, Punjab Pakistan: Teachers Problems and Prospects. Study employed a descriptive quantitative design. The population of the study was all the mathematic teachers of grade three at public primary schools and random sampling technique was used for sample selection. The sample (210) represents 30% of the population. The self-developed Likert type questionnaire was used to collect data. A questionnaire was about students’ mathematical rigor with 18 items. The value of Cronbach’s alpha for students’ mathematical rigor questionnaire was 0.89. The findings revealed that most of the teachers perceived that they have good level to foster student’s mathematical rigor. Results indicated that students possess a noteworthy degree of mathematical rigor, which were shown by their solid conceptual understanding of mathematical ideas, high level of fluency, and fluent application of these concepts. However, the range of differences identified in fluency and application scores highlights the need for ongoing endeavours to guarantee uniformity and thoroughness in mathematical skills across various situations. Key words: Mathematical Rigor, Conceptual Understanding, Fluency, Application, Primary School Teachers